Illegitimate authority facing the challenges of our time - Polychroniou, Chronis; Polychroniou, Chronis (Haymarket Books, 2023)
"In these informative interviews, conducted for Truthout by C.J. Polychroniou, Noam Chomsky addresses the rapid deterioration of democracy in the United States and rising tensions globally. He examines the crumbling social fabric and fractures of the Biden era, including the halting steps toward a Green New Deal; the illegitimate authority of the Supreme Court, in particular its decision to overturn Roe vs. Wade; and the ongoing fallout from COVID-19. Chomsky also untangles the roots of the War in Ukraine, the diplomatic tensions among the United States, China, and Russia, and considers the need for climate action on an international scale." -- Provided by publisher
"A Truthout collection"-- Cover
Keywords: Soziale Situation; Demokratie; Krise; Green New Deal; Russisch-Ukrainischer Krieg; Gesellschaft; USA; Geopolitics / United States / History / 21st century; Democracy / United States / History / 21st century; Democracy; Geopolitics; United States; 2000-2099; History; Interviews; Interview